2016
DOI: 10.1002/cctc.201600035
|View full text |Cite
|
Sign up to set email alerts
|

Oxime‐Derived Palladacycles: Applications in Catalysis

Abstract: Abstract:Phenone oxime-derived palladacycles are stable, easy to prepare and excellent source of three-and four-atom Pd clusters able to show excellent catalytic activity in most of the classical carbon-carbon bond forming reactions (Mizoroki-Heck, Matsuda-Heck, Suzuki-Miyaura, Stille, Kumada, Hiyama, Ullmann, Sonogashira and Glasser) in general with better performance than Pd(OAc)2 or other Pd salts. Aryl iodides, bromides, chlorides and imidazolyl sulfonates can be used as substrates not only in organic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 112 publications
1
35
0
Order By: Relevance
“…The plausible reaction mechanism of oxime palladacycle (1) catalyzed phenoxycarbonylation for ester synthesis is shown in Scheme . Initially, Pd (0) insert between aryl iodide via breaking of C‐I bond to the formation of species B . Then CO (g) coordinate with aryl palladium species ( B ) to give C .…”
Section: Resultsmentioning
confidence: 99%
“…The plausible reaction mechanism of oxime palladacycle (1) catalyzed phenoxycarbonylation for ester synthesis is shown in Scheme . Initially, Pd (0) insert between aryl iodide via breaking of C‐I bond to the formation of species B . Then CO (g) coordinate with aryl palladium species ( B ) to give C .…”
Section: Resultsmentioning
confidence: 99%
“…1 H-NMR (300 MHz) and 13 C-NMR (75 MHz) spectra were obtained on a Bruker AC-300, using CDCl3 as solvent and TMS (0.003%) as reference, unless otherwise stated. Low-resolution mass spectra (MS) were recorded in the electron impact mode (EI, 70 eV, He as carrier phase) using an Agilent 5973 Network Mass Selective Detector spectrometer, being the samples introduced through a GC chromatograph Agilent 6890N equipped with a HP-5MS column [(5%-phenyl)-methylpolysiloxane; length 30 m; ID 0.25 mm; film 0.25 mm].…”
Section: Generalmentioning
confidence: 99%
“…Carbometallated Pd(II) compounds, especially the highly active palladacycles [10][11][12][13], have emerged as very promising catalysts for C-C bond forming reactions. These complexes usually involve very low catalyst loadings, minimizing the cost-effective impact of the expensive palladium.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization is a method to improve catalytic activity and recyclability of homogeneous catalysts using an appropriate supporting system such as polymers, resins etc. [39][40][41][42] However, it has been reported that palladium immobilization is generally complicated and involves multiple steps with undesirable palladium black formation and relatively long reaction times. [40,41] In our previous work, we investigated the catalytic activity of N-phthalimidoethyl and 4-substituted benzylbearing benzimidazolium salts in the Sonogashira crosscoupling reaction.…”
Section: Introductionmentioning
confidence: 99%